Calculative Practices in International Environmental Governance: In (Partial) Defence of Indicators. Issue 2 (19th July 2020) - Ellis, Jaye
Abstract: The role of calculative practices such as goals and indicators in international environmental governance causes concern among many observers, who view them as promoting a reductivist approach to the non-human world and privileging economic understandings of environmental governance above all others. Yet they possess enormous potential to provide insights into the non-human world that could be of great benefit to governance. This article takes seriously critical perspectives of calculative practices, while exploring a weakness in much of the critical literature, namely a failure to examine assumptions about the nature of scientific knowledge and the manner in which it is, and ought to be, taken up by policy makers. I contend that both the design of environmental regimes and critical analyses of these regimes bear the marks of the influence, albeit indirect, of early 20 th century views on the superiority of scientific knowledge and its unique capacity to ground decision making. I argue that a richer, more nuanced account of the co-production of ecological metrics such as goals and indicators and their potential contributions to ecosystem governance and sustainability is necessary. With such accounts, scholars and political authorities would be in a better position to address the very real pitfalls and dangers of calculative practices while not feeling compelled to forego these potentially powerful approaches.